Experimental and Theoretical Studies of Serpentine Interconnects on Ultrathin Elastomers for Stretchable Electronics. (4th August 2017) - Pan, Taisong; Pharr, Matt; Ma, Yinji; Ning, Rui; Yan, Zheng; Xu, Renxiao; Feng, Xue; Huang, Yonggang; Rogers, John A.
Abstract : Integrating deformable interconnects with inorganic functional materials establishes a path to high‐performance stretchable electronics. A number of applications demand that these systems sustain large deformations under repetitive loading. In this manuscript, the influence of the elastomeric substrate on the stretchability of serpentine interconnects is investigated theoretically and experimentally. Finite element analyses (FEA) reveal a substantial increase in the elastic stretchability with reductions in substrate thickness. Low‐cycle fatigue tests confirm this trend by examining the stretch required to form fatigue cracks associated with plastic deformation. To elucidate the mechanics governing this phenomenon, the buckling behaviors of deformed serpentine interconnects on substrates of various thicknesses are examined. The analytical model and FEA simulations suggest a change in the buckling mode from local wrinkling to global buckling below a critical thickness of the substrate. Scanning electron microscope and 3D optical profiler studies verify this transition in buckling behavior. The global buckling found in thin substrates accommodates large stretching prior to plastic deformation of the serpentines, thereby drastically enhancing the stretchability of these systems. Abstract : A competition between the length of the straight segment of an interconnect and a critical length governed by the thickness of substrate determines the buckling mode of serpentine interconnects on elastomeric substrates, resulting in a significant increase in the elastic stretchability of the interconnects by reducing substrate thickness.